Economic Assessment of Sanitation Interventions in the Philippines - World Bank (Washington, DC, 2014)
The Philippines is well on its way to achieving the sanitation target, which is part of a combined drinking water and sanitation target within the Millennium Development Goal (MDG). As of 2008, about 76 percent of its population had access to improved sanitation facilities (JMP 2010). This is nearly 18 percentage points higher than the estimates for 1990 and 3 percentage points short of the MDG target for sanitation. This study aims to generate evidence on the costs and benefits of sanitation improvements in different contexts in the Philippines. Conducted with a view towards identifying the most economically efficient options under different conditions, it aims to contribute to the decision making processes of government, donor agencies, and non-governmental organizations (NGOs) and other institutions. The study quantified the costs and benefits associated with various sanitation options in different study sites. The benefits included the impacts on health, water sources and treatment, access time, and the reuse of human excreta. The costs included capital or investment costs and the recurrent costs associated with various sanitation options. The costs and benefits of the sanitation options were synthesized using standard indicators of economic efficiency. These indicators included the benefit-cost ratio, cost-effectiveness ratio, net present value, internal rate of the return, and payback period of sanitation options. Cost-effectiveness ratios cost per disability life year averted, cost per disease case averted, cost per death averted were also calculated.